Gender perceptions on digital platforms: A study on TikTok users' awareness of gender roles - KARADUMAN, Sibel; Kayitmazbatir, Güzide; Karaduman, Murad; ŞEN, Elif Pınar ACİYAN (Edelweiss Applied Science and Technology, 2026)
Digital platforms significantly influence gender awareness and perceptions, serving as spaces where gender roles are both reinforced and challenged. TikTok, one of the most popular platforms where users can create content, employs short videos and personalized algorithms to shape social dynamics. As digital natives, Generation Z forms the primary audience globally. This study investigates how young TikTok users in Turkey perceive and interpret gender roles and representations within platform content. Using a qualitative approach, semi-structured in-depth interviews were conducted with 15 undergraduate students, and data were analyzed through thematic analysis. Results show that participants are highly aware of gender roles depicted on TikTok, but their interpretations generally align with traditional gender norms. The content often reproduces dominant stereotypes: female representations emphasize beauty, personal care, and daily routines, while male portrayals focus on power, authority, and public participation. The study also reveals that participants critically recognize how algorithms influence their digital experiences. Despite the prevalence of traditional roles, users maintain a strong critical perspective. These findings provide valuable insights for developing media literacy programs and promoting more inclusive gender representations on digital platforms.